Pandangan Guru tentang Efektifitas Pembelajaran Matematika dalam Optimalisasi Kesehatan Intelektual Anak dengan Disabilitas Mental - Ayuni, Anggun; Kusuma, Anggi; Palupi, Rini; Kameliawati, Feri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2025)
Functional limitations in various aspects of children with mental disabilities are a challenge for special school teachers in achieving learning objectives. Mathematics subjects often present difficulties for students without mental disabilities, let alone children with mental disabilities, so this is a challenge for teachers. The purpose of this study was to describe the experiences of teachers in the process of teaching mathematics to children with special needs. This research was a qualitative study with a phenomenological approach. Informants were selected by snowball sampling, namely 3 mathematics teachers. Data were collected through in-depth interviews. Data analysis was carried out using the Miles & Huberman model, namely data reduction, data presentation and drawing conclusions. The results of this study revealed that teachers' experiences in utilizing mathematics learning media for children with special needs consist of 4 themes: support, obstacles, and teacher strategies, as well as the role of parents. Based on teacher presentations, it was found that teacher support for children with special needs is by giving appreciation and praise during the learning process; obstacles faced are the child's mood so that teachers must be extra patient in teaching; strategies used by teachers, especially picture media; making the classroom comfortable can help the learning process for children with special needs; The role of parents is essential for repeating learning at home. Furthermore, four key factors are needed for effective learning: appreciation and praise, the child's mood as a major obstacle, making learning more engaging, and the role of parents in repetition.Keywords: children; mental disabilities; learning; mathematics; teachers ABSTRAK Keterbatasan fungsi dari berbagai aspek pada anak dengan disabilitas mental merupakan tantangan bagi guru sekolah luar biasa untuk mencapai tujuan pembelajaran. Mata pelajaran matematika banyak menyulitkan siswa tanpa disabilitas mental, apalagi anak dengan disabilitas mental, maka ini menjadi tantangan tersendiri bagi guru. Tujuan penelitian ini adalah menggambarkan pengalaman guru dalam proses pembelajaran mata pelajaran matematika pada anak berkebutuhan khusus. Penelitian ini merupakan studi kualitatif dengan pendekatan fenomenologi. Informan dipilih dengan snowball sampling, yakni 3 guru pengajar matematika. Data dikumpulkan melalui wawancara mendalam. Analisis data dilakukan dengan model Miles & Huberman yaitu reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini mengungkapkan bahwa pengalaman guru dalam pemanfaatan media pembelajaran matematika pada anak berkebutuhan khusus terdiri atas 4 tema yaitu dukungan, hambatan, dan strategi guru, serta peran orangtua. Berdasarkan pemaparan guru, didapatkan bahwa dukungan guru bagi anak berkebutuhan khusus adalah dengan cara memberikan apresiasi pujian pada saat proses pembelajaran; hambatan yang dihadapi yaitu mood anak sehingga guru harus ekstra sabar dalam mengajar; strategi yang digunakan oleh guru terutama media gambar; membuat kelas menjadi nyaman dapat membantu proses pembelajaran bagi anak berkebutuhan khusus; dan peran orangtua sangat diperlukan untuk pengulangan pembelajaran di rumah. Selanjutnya disimpulkan perlunya 4 poin efektivitas pembelajaran yaitu apresiasi pujian, mood anak merupakan hambatan utama,  membuat pembelajaran lebih menarik dan peran orang tua dalam pengulangan.Kata kunci: anak; disabilitas mental; pembelajaran; matematika; guru